Pengimplementasian Karakter Nasionalis Siswa di Kelas VI SD - Chendi Maulana Baharudin Yusup; Dinie Anggraeni Dewi (Departement of Mathematics Education, 2021)
This study aims to improve nationalist character education for students, especially in grade VI elementary schools. This type of research is qualitative research, which focuses on the implementation of naationalist character education in grade VI SD. Nationalist character education for elementary school children, especially in grade VI, is a process of fertilizing from an early age for them. In nationalist character education there are civic education subjects that teach the values contained in Pancasila and teach and educate students to become individuals who have habits of national character in their daily lives. Seeing the current condition of children, students have decreased in terms of implementing national character in their lives. Therefore, schools through civic education are expected to be able to train and educate students so that students have a nationalist attitude in their lives. A nationalist attitude is an understanding attitude that has cultural and regional harmony. They also have the same ideals and goals so that they feel the desire to defend their country, both from internal and external threats.